The development of a rapid self-healing semiconducting monoethanolamine-based Mg(OH)2 metallogel for a Schottky diode application with a high ON/OFF ratio. (19th September 2019) - Dhibar, Subhendu; Dey, Arka; Dey, Amiya; Majumdar, Santanu; Mandal, Amit; Ray, Partha Pratim; Dey, Biswajit
Abstract : A rapid self-healing Mg(OH)2 metallogel developed by mixing monoethanolamine and an Mg(ii ) salt offers a Schottky barrier diode device with a high ON/OFF ratio. Abstract : An intriguing rapid self-healing functional Mg(OH)2 metallogel was instantaneously developed through the direct mixing of monoethanolamine and magnesium nitrate hexahydrate as the source of magnesium ions in a water medium at room temperature under atmospheric pressure. The rheological properties of the Mg(OH)2 metallogel were scrutinized, and this revealed the mechanical toughness of the semi-solid metallogel material. The outcome of the rheological experiment showed the self-healing property of the metallogel. The self-healing feature was rapid and it occurred within a few minutes of the insertion of a crack into the metallogel or the association of two separate metallogel parts. The morphology of the metallogel was visualized through field emission scanning electron microscopy and EDX spectral investigations. The experimentally estimated optical band gap suggested the semiconducting nature of the material. The semiconducting nature of the metallogel was further verified from the electrical properties. Finally, a technologically challenging device-type application was also realized by the successful fabrication of a Schottky barrier diode, and different device parameters were investigated to verify the performance. The fabricated diode based on the Mg(ii ) metallogel showed a very high ON/OFF ratio of 85.52.